Different life‐form strategies of perennial energy crops and related nutrient exports require a differentiating view specifically concerning a sustainable cultivation on marginal land. Issue 6 (3rd May 2021) - Ruf, Thorsten; Emmerling, Christoph
Abstract: Perennial energy crops (PECs) are increasingly used as feedstock to produce energy in an environmental friendly way. Compared to traditional conversion strategies like thermal use, sophisticated technologies such as biomethanation defined different requirements of the feedstock. Whereas the first concept relies on dry, woody material, biomethanation requires a moist feedstock. Thus, over time, the spectrum of species used as PECs has widened. Moreover, harvest dates were adjusted to provide the feedstock at suitable moisture contents. It is well known that perennial, lignocellulose‐based energy crops, compared to annual, sugar‐ and starch‐based ones, offer ecological advantages such as, inter alia, improving biodiversity in landscape, protecting soil against erosion, and protecting groundwater from nutrient inputs. However, one of the main arguments for PEC cultivation was their undemanding nature concerning external inputs. With respect to the broader spectrum of PEC species and changed harvest dates, the question arises whether the concept of PECs being low‐input energy crops is still valid. This also implies the question of suitable growing conditions and sustainable management. The aims of this opinion paper were to classify different PECs according to their life‐form strategy, compare nutrient exports when harvested in different maturation stages, and to discuss the results in the context of sustainable PEC cultivation on marginal land. This study revealed that nutrient exports with yield biomass of PECs harvested in green state are in the same range than those of annual energy crops and therewith several times higher than those of PECs harvested in brown state or of woody short rotation coppices. Thus, PECs cannot universally be claimed as low‐input energy crops. These results also imply the consequences of cultivation of PECs on marginal land. Finally, the question has to be raised whether the term PECs should prospectively be better specified in written and spoken words. Abstract : Newly introduced utilization pathways of perennial energy crops have led to the cultivation of different crop species like cup plant and for traditional crops like Miscanthus to preponed harvest dates in green, immature states. Existing studies were evaluated concerning nutrient exports with yield biomass and discussed against the concept of perennial energy crops presenting low‐input systems. It could be shown that the vegetative life‐form strategy and harvesting dates of the crops significantly affect nutrient exports and their suitability for cultivation on marginal land. The authors suggest a more differentiated view on the requirements of perennial energy crops.